2009
DOI: 10.1111/j.1365-2982.2008.01224.x
|View full text |Cite
|
Sign up to set email alerts
|

Galanin modulates vagally induced contractions in the mouse oesophagus

Abstract: Nitrergic myenteric neurons co-innervating motor endplates were previously shown to inhibit vagally induced contractions of striated muscle in the rodent oesophagus. Immunohistochemical demonstration of putative co-transmitters, e.g. galanin, in enteric neurons prompted us to study a possible role of galanin in modulating vagally mediated contractions in an in vitro vagus nerve-oesophagus preparation of the mouse. Galanin (1-16) (1-100 nmol L(-1)), in the presence of the peptidase inhibitor, phenanthroline mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 40 publications
0
21
0
Order By: Relevance
“…Spontaneous intestinal contractions of circular muscle were recorded as described previously (Penuelas et al, 2007;Boudaka et al, 2009). Briefly, 8-to 12-week-old male WT mice were killed by cervical dislocation.…”
Section: Methodsmentioning
confidence: 99%
“…Spontaneous intestinal contractions of circular muscle were recorded as described previously (Penuelas et al, 2007;Boudaka et al, 2009). Briefly, 8-to 12-week-old male WT mice were killed by cervical dislocation.…”
Section: Methodsmentioning
confidence: 99%
“…Morphological studies have shown that esophageal striated muscle receives dual innervation from both vagal motor fibers originating in the brainstem and varicose intrinsic nerve fibers originating in the myenteric plexus, which is called “enteric coinnervation” of esophageal motor endplates [3, 17]. We have also provided evidence that a local neural reflex pathway in the esophagus, consisting of primary afferent neurons and myenteric neurons, can modulate motility of the striated muscle portion of the esophagus [1821]. Thus, both extrinsic and intrinsic neural regulations would be important in coordinating the peristaltic motility of the esophagus.…”
Section: Introductionmentioning
confidence: 99%
“…The release of galanin can also be detected in vitro but at lower levels than that observed for NPY (39). Evidence for galinin release as a cotransmitter under conditions of high sympathetic stimulation has also been reported within the liver and the gut (7,51) Antagonists of the Y 2 receptor and GALR1 can reverse the inhibition of vagal bradycardia inhibition postsympathetic stimulation in vitro (39) and in vivo (104) as can genetic knockout of these receptors in vivo (88,105,106). Immunohistochemical labeling has localized the NPY Y 2 receptor (41) as well as the galanin GalR1 receptor (39) to vagal neurons in the right atria and around the sinoatrial node providing the anatomical basis for the sympathovagal cross-talk model.…”
Section: Indirect Consequences Of Sympathetic Hyperactivity: Sympathomentioning
confidence: 83%